EFEKTIVITAS MODUL GIZI SEIMBANG DAN BAHAYA ANEMIA DALAM MENINGKATKAN PENGETAHUAN MAHASISWA ASIA UNIVERSITY TAIWAN - Anditri Weningtyas; Kiky Martha Ariesaka; Lintang Widya Sishartami; Hilma Tsurayya; Iftitahurroza Iftitahurroza; Arif Ladika; Fannia Yosa Bakhtiar (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
The objective of this study was to evaluate the impact of utilizing balanced nutrition and anemia awareness modules as socialization media on the knowledge levels of university students in Taiwan. Balanced nutrition is a critical element for maintaining optimal health, especially among students who often face academic and social pressures. This socialization initiative aimed to provide a deeper understanding of the importance of balanced nutrition and anemia prevention to enhance awareness and knowledge among students. The study employed a quantitative approach involving 32 students from Asia University College of Medical and Health Sciences as participants. Data were collected through pre-tests and post-tests using a questionnaire comprising 10 questions to assess knowledge levels before and after the intervention. The data were analyzed using the Wilcoxon test with SPSS software to identify significant differences in knowledge scores. The results revealed a significant improvement in the students' knowledge after the socialization program. Before the intervention, the average knowledge score of the participants was 22.4 ± 6.93. Following the intervention, the score increased to 15.8 ± 6.53, with a p-value of 0.005, indicating the program's success. In conclusion, the balanced nutrition module proved to be an effective socialization tool for enhancing students' understanding of anemia prevention and the importance of healthy eating habits. Recommendations from this study include the development of more interactive modules and the implementation of continuous educational programs to ensure long-term improvements in students' comprehension of balanced nutrition and anemia prevention.